PANCASILA DALAM KONTEKS PENDIDIKAN NILAI - Toni Nasution (Jurnal Al-Fatih, 2019)
The educational world has signs which became a reference for a goal that must be achieved nationally, that in a sense is very important and interesting for the mind that 1945 Preamble explicitly mentions about "the intellectual life the nation "as one of the objectives of the formation of the Government of our country based on the Pancasila. In other words one of the ideals of freedom that was about to be realized with the formation of the Government of our country is accomplishing the life of the nation Indonesia. Pancasila education in the context of the value of being a national education goals hatched in the perspective of standards of conduct. Size that determines a person's personality criteria precisely the characters into a color against the behavior of someone. Thus in the context of pancasila values education is basically a process of internalization of values against the students that students can understand, appreciate and do practice the values of pancasila and behave in a He thought well and does not conflict with the norms in force.